(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
The objective of the research is to design a model of urban sustainability indicators to strengthen the local development of the canton of La Libertad; urban sustainability indicators have been seen as signals that mark the progress of the achievement of the objectives and goals set in the urban planning process, and allow making relevant and timely decisions. The types of research used are descriptive and analytical, by measuring variables through the deductive and inductive methods; a population of 48671 was considered, corresponding to the number of inhabitants of the canton of La Libertad between the ages of 20 and 64, from which a sample of 356 people was selected. The proposed model MSUCLL - 2021, is a model determined in relation to the criteria determined in the research, thus allowing the improvement of critical factors that affect urban sustainability; it includes 4 axes: compactness and functionality, urban complexity, efficiency, and social cohesion.